User’s satisfaction with the performance of wet markets in Shah Alam, Selangor / Md Faaiz Md Boizi - Md Boizi, Md Faaiz (Faculty of Architecture, Planning and Surveying, 2014)
Wet market. All of us already know what wet market is. Wet market is very important to a society because this is a place where you can see the culture of the place while you bought things like fresh meat, fresh fish there. Wet market is also a gathering place where every day visitors will visit this place to buy wet ingredients. Wet market can be one of ‘must visit’ place especially tourist from all over the world. Malaysia for one, has received its fair bit of positive publicity from it. With greater recognition of the importance of tourism, more and more countries are pumping resources to develop and improve infrastructure, in hope of attracting visitors including local visitors. However, in doing so, many lead to overlook the importance of wet market. We can see the existing wet market still sad and very bad performance in terms of thermal comfort. This dissertation addresses the users’ satisfaction on the performance of wet markets at Shah Alam, Selangor Darul Ehsan. A questionnaire survey was conducted on a sample size of 20 visitors in three different case studies to find out their satisfaction and their awareness toward performance of wet market. In addition, we asked for their feedback and recommendation for improvement. Conclusion was made based on result analysis data findings. At the end of this research, the data that been analyze then can be concluded in recommendations to overcome the problem that occur based on the dissertation’s aim.